Jumlah Langsung Subsemimodul Prima - Andi Muhammad Anwar; Hanni Garminia; Irawati Irawati (Jurnal Matematika, Statistika dan Komputasi, 2022)
Let be a commutative semiring. A semimodule over a semiring is a fully prime semimodule if each proper subsemimodule of is prime. This research aims to investigate the relationship between a direct sum of prime subsemimodules and , , and a fully prime semimodule.